Water security for Palestinians and Israelis: Towards a new cooperation in middle east water resources - Ward, Christopher; Ruckstuhl, Sandra & Learmont, Isabelle (Dublin I. B. Tauris; Bloomsbury, 2022)
Shared water resources in Israel and Palestine are often the site of political, economic, historical, legal and ethical contestation. In this, the second of two volumes on the subject, the authors look beyond the political tensions of the region, to argue for the need for shared water security and co-operative resource management. Winning Water Security for Palestinians and Israelis, the authors assess water security in terms of security of access to water resources, security of access to water services and security against risks to and from water. The volume compares and contrasts Israelis remarkable water security with the corresponding water insecurity of the Palestinians. The authors also set out the practical, economic, legal and ethical rationale for a revised cooperation on water security between the two peoples, proposing a workable scheme for putting into practice a new form of cooperation that would hope to benefit both peoples and strengthen their water security.
Keywords: Security and Foreign Affairs Sector; Water Resources; Water Security & cooperation